2022
DOI: 10.1002/pmrj.12862
|View full text |Cite
|
Sign up to set email alerts
|

Surgery to restore upper extremity function in tetraplegia—Preferences for early and frequent access to information

Abstract: Introduction People with cervical spinal cord injury (SCI) identify improving upper extremity (UE) function as a top priority. In addition to comprehensive rehabilitation, UE surgeries, including nerve and tendon transfers, enhance function. However, barriers exist to disseminating information about surgical options to enhance UE function. Objective To assess the experiences and preferences of people with cervical SCI and their caregivers in accessing information about surgery to enhance UE function. Design Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…5,30,31,34 People with spinal cord injury use the Internet but also rely on getting information from their trusted healthcare providers-physical medicine and rehabilitation, spinal cord injury specialists, and occupational and physical therapists, among others. 29 These nonsurgeon clinicians often lack access to information and knowledge about these treatment options and may have biases against some or all of these surgical treatments. 33,58,59 A recent United States study found that only 8% of eligible individuals underwent this restorative surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,30,31,34 People with spinal cord injury use the Internet but also rely on getting information from their trusted healthcare providers-physical medicine and rehabilitation, spinal cord injury specialists, and occupational and physical therapists, among others. 29 These nonsurgeon clinicians often lack access to information and knowledge about these treatment options and may have biases against some or all of these surgical treatments. 33,58,59 A recent United States study found that only 8% of eligible individuals underwent this restorative surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The determination to create an online tool was informed by our previous research, which showed that people with spinal cord injury prefer the use of computers, phones, and tablets for accessing health information. 29 The content of the PtDA was informed by the current literature, results from the European Multicenter Study about Spinal Cord Injury (EMSCI), 39 and a prospective mixed-methods cohort study of people living with cervical spinal cord injury (who did and did not undergo surgery) and their caregivers. 40 – 42 Information was summarized and incorporated into the PtDA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation